1975
DOI: 10.1177/001440297504100601
|View full text |Cite
|
Sign up to set email alerts
|

Research Implications for Communication Deficiencies

Abstract: This article traces, historically, four decades of chimpanzee research relevant to the prosthesis of communication deficiencies. The prosthetic methods reviewed include the following: (a) environment and specialized prosthetic training, (b) mechanical devices for the production of expressive speech, (c) learning of sign systems, e.g., American Sign Language, and (d) a language system based on nonspeech manipulable symbols. The knowledge and techniques resulting from the chimpanzee research have been applied to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1977
1977
1980
1980

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Where these skills are not present they may be taught before the language sessions begin, although our experience indicates that they may be learned concurrently with the Rebus language. A number of studies of this type have now been reported (Glass, Gazzaniga & Premack 1973, Premack & Premack 1974, Blain 1975, Hollis & Carrier 1975, Carrier 1976, Deich & Hodges 1977, although only Blain has used rebuses.…”
mentioning
confidence: 99%
“…Where these skills are not present they may be taught before the language sessions begin, although our experience indicates that they may be learned concurrently with the Rebus language. A number of studies of this type have now been reported (Glass, Gazzaniga & Premack 1973, Premack & Premack 1974, Blain 1975, Hollis & Carrier 1975, Carrier 1976, Deich & Hodges 1977, although only Blain has used rebuses.…”
mentioning
confidence: 99%